Community Ageing With Health And Dignity Through A Service-Learning Initiative - Hiu Lam Yee; Ben Y.F Fong; Tommy K.C NG; Billie S.M Chow (ACHSM, 2020)
Background: A new compulsory service-learning subject was introduced in the Practices of Health Promotion module of Bachelor of Science in Applied Sciences (Health Studies), run by School of Professional Education and Executive Development, The Hong Kong Polytechnic University. It aims to develop students' ability to apply learned principles and concepts of health behaviour from lectures into a community setting, by completing elderly site services arranged at four selected elderly centres. Methods: 36 students were enrolled in the subject. An analytical framework was developed based on specific themes, sub-categories and categories. Data extracted from students' reflective journals were input into a qualitative analysis software, Qualitative Data Analysis (QDA) Miner 5 of Provalis Prosuite for analysis.  Results: 5 themes and 24 categories were created based on the data analysed from students' reflective journals. The three highest frequency themes are 'Skills learned' (170 text units, 32.6% of total), 'Challenges' (140 text units, 26.8% of total), and 'Elders characteristics' (135 text units, 25.9% of total). Conclusions: Communication, teamwork and organising activities to the elderly are the most cited skills learned by students. They have also identified elders' personality and characteristic when communicating with them. Although there were challenges when interacting with the recipients and centres, students have overcome most of them and have learned better ways to communicate with elders and reacted quickly by changing the content of designed activities provided to elders.